(untitled) (المجلة الدولية للعلوم المالية والإدارية والاقتصادية, 2026)
This paper evaluates how efficiently Gulf Cooperation Council (GCC) countries transform knowledge‑system inputs into knowledge capabilities and, ultimately, into knowledge‑based economic performance, using the Global Knowledge Index (GKI) as an integrated input–output framework over the period 2021–2024. Building on a two‑stage network Data Envelopment Analysis (DEA) model fully embedded in the GKI architecture, Stage 1 measures knowledge‑formation efficiency in converting education, TVET, higher education, RDI, ICT, and enabling‑environment pillars into composite intermediate knowledge outputs, while Stage 2 assesses knowledge‑to‑economy conversion efficiency in translating these outputs into the GKI economy indicator and its pillars of competitiveness, openness, and domestic value added. The results reveal substantial cross‑country heterogeneity: the United Arab Emirates and Qatar operate on the efficiency frontier in both stages, whereas Saudi Arabia, Kuwait, Bahrain, and Oman exhibit significant input surpluses and output shortfalls, especially in higher education, RDI, and value‑added generation, indicating structural gaps between knowledge formation and economic absorption. To assess the feasibility of achieving Vision 2030 targets, the study introduces a Δθ‑based forecasting model that quantifies the annual efficiency improvements required for each country to reach frontier or high‑performance thresholds (0.90–0.95) by 2030 and develops a policy‑intensity framework that maps these efficiency gaps into differentiated reform pathways ranging from light to transformational interventions. By extending DEA from static benchmarking to forward‑looking efficiency trajectories, the paper contributes to the technological forecasting and social change literature by offering a GKI‑consistent, multi‑stage efficiency framework that can be used to monitor progress toward national vision targets, stress‑test policy scenarios, and inform strategic planning for knowledge‑based diversification in resource‑rich economies.